Voices' use of gender, race and other social categories to undermine female voice-hearers: Implications for incorporating intersectionality within CBT for psychosis. Issue 3 (2nd July 2016) - Haarmans, Maria; Vass, Victoria; Bentall, Richard P.
Abstract : Great strides have been made in understanding the impact of social inequality on the risk of developing psychotic experiences. However, little is known about the influence of intersecting social categories such as gender, race and class on the experience and expression of psychotic phenomena. Intersectionality, a framework recently advanced in psychology, examines the joint impact of multiple forms of marginalisation on well-being. We adopted this approach to develop a codebook and analyse the voice content of 44 women diagnosed with schizophrenia for the ways in which social categories are used to undermine and/or affirm voice-hearers. Over half of the sample included women with ethnic-minority status. The coding system was reliable. Gendered conditions of worth were used by voices to undermine by far the majority (40) of women and racialised conditions of worth over half (14) the ethnic-minority women. We conclude that voice content often reflects social categories and structural inequalities in society and discuss implications for CBT for psychosis when working with women of majority and ethnic-minority statuses.